Ministerial decree no. 423/2016 amending article (22) of the statute of rules enforcing the provisions of the import and export law = قرار وزاري رقم 423 لسنة 2016 بتعديل المادة (22) من لائحة القواعد المنفذة لأحكام قانون الاستيراد والتصدير - Egypt. Ministry of trade and industry. The Egyptian Customs Authority (2025)
Ministry of Trade and Industry decree no. 423 of the year 2016 amending article (22) of the statute of rules enforcing the provisions the import and export law وزارة التجارة والصناعة قرار رقم 423 لسنة 2016 بتعديل المادة (22) من لائحة القواعد المنفذة لأحكام قانون الاستيراد والتصدير